Peatland vegetation organization and dynamics in the western subarctic, Northwest Territories, Canada - Jasieniuk, M. A.; Johnson, E. A. (Canadian Journal of Botany, 1982)
Species frequency abundance was determined in 77 peatland stands and the variance partitioned between the effects of fire and habitat. Each variance partition was then analyzed using principal component analysis. The resulting habitat ordination was interpreted in terms of a moisture–nutrient gradient and a sphagnum substrate gradient. The fire frequency ordination gave a gradient of plant adaptations to the interval between fires. Vegetation change after fire is predominantly change in species abundance. It consists of a regeneration to the predisturbance species composition which depends on the moisture–nutrient and sphagnum substrate conditions. Changes in species composition are suggested to be due to major changes in habitat characteristics usually the result of water level fluctuations. A discussion of the frequency of disturbance due to water level fluctuations and fire for different peatland communities is presented.